On the history of clause-final negation in the Mande languages of the Bani - upper Mouhoun rivers area - (:unkn) unknown (My University, 2012)
As argued by Idiatov (2011), clause-final negation markers common in the languages of northern sub-Saharan Africa typically develop within already negative constructions as secondary negation markers out of clause-final (inter)subjective markers. These markers with clausal scope and syntactically oriented to the clause as a whole, feature prominently in many languages of the area. In the literature, they have been variously referred to as (sentence, clause, utterance) modal, epistemic, emphasis, discourse or conversational markers (particles, adverbs), to mention just some terms.The hypothesis relating clause-final negation markers to equally clause-final (inter)subjective markers accounts for the frequent clause-final position of negation markers in the languages of this zone, which is otherwise typologically unusual (cf. Dryer 2009). Furthermore, it allows for a better understanding of several other peculiarities of negation markers in the languages of this zone, such as the frequent occurrence of multiple negative exponence, the fact that clause-final negation markers tend to be diachronically unstable and appear to be relatively easily borrowable, unlike negators in other parts of the world, but like discourse markers, focus particles and phasal adverbs (cf. Matras 2009). Several particularly instructive examples of the aforementioned phenomena are provided by Mande languages, where clause-final negation markers are not uncommon. In my paper, I focus on evidence from several Mande languages spoken in the Bani - upper Mouhoun rivers area, such as Bobo, Samo, varieties of Manding and languages of the Samogo group. In particular, I discuss the evolution of clause-final negation markers in these languages, highlighting their relation with clause-final (inter)subjective markers and analyzing the role of language contact in their development in some of these languages.
Keywords: African Research